A legalidade da atuação da guarda municipal como agente de educação ambiental - Silva, Ygor Felipe Távora Da (2019)
With population growth and the accentuation of environmental degradation, new legal and constitutional aspects ensured tools that foment the mitigation of impacts caused by human interaction with the environment. In an attempt to protect and conserve natural resources, the practice of public education policies ensures a fundamental prism preventive vision held by the public authorities primarily through environmental education, for reflecting and objectify an awareness in the different education levels, surpassing the academic limits and allowing the performance of new educational agents, through direct interaction with the community, conveying an empirical knowledge, local and traditional within the protected areas. However, due to significant population mass present in large urban centers, almost expressionless, centralized environmental education by a single agency manager, should allow, at the municipal level, the interaction of all the actors responsible for public property protection, especially for the preventive action of institutions such as the Municipal Guard Manaus, responsible, including the urban environment, as provided by the very Statute of the Municipality, which asserts the formation of a specialized body to safeguard the environmental heritage and legally enables the formation of agents educators within the Municipal Protected Areas. This thesis has the primary objective to study a proposal for a program that enables the performance of the Municipal Guards, through environmental education, and their preventive actions to safeguard the environment, the harmonic performance of their duties by the Municipal Department of Environment and sustainability. The specific objectives are: Set the jurisdiction of the Metropolitan Guard and its activities in the city of Manaus protected areas; Identify the preventive measures already in place between the Metropolitan Guard and the Municipal Environment and Sustainability; Describe the elements of management, public policy and legislation to an applicable interagency program within the Municipal Protected Areas. The methodology was qualitative research with exploratory and descriptive character. It is concluded that the Municipal Guard currently has a protective function and surveillance of public property. However, the guards target a higher profile by acting as environmental education officers, describing the relevance of its functions to the protection of the Environment and disseminating scientific and traditional knowledge to society.